Participation in and adherence to physical exercise after completion of primary cancer treatment. Issue 1 (December 2016) - Kampshoff, Caroline; Mechelen, Willem; Schep, Goof; Nijziel, Marten; Witlox, Lenja; Bosman, Lisa; Chinapaw, Mai; Brug, Johannes; Buffart, Laurien
Abstract Background ﻿The purpose of this study was  to identify demographic, clinical, psychosocial, physical and environmental factors that are associated with participation in and adherence to a combined resistance and endurance exercise program among cancer survivors, shortly after completion of primary cancer treatment. Data from the randomized controlled Resistance and Endurance exercise After ChemoTherapy (REACT) study were used for this study. Methods The participants of the REACT study were randomly allocated to either a high intensity (HI) or low-to-moderate intensity (LMI) exercise program. Patients' participation rate was defined as the cancer survivors' decision to participate in the REACT study. Exercise adherence reflected participants' attendance to the scheduled exercise sessions and their compliance to the prescribed exercises. High session attendance rates were defined as attending at least 80 % of the sessions. High compliance rates were defined as performing at least of 90 % of the prescribed exercise across all sessions. Correlates of exercise adherence were studied separately for HI and LMI exercise. Demographic, clinical, and physical factors were assessed using self-reported questionnaires. Relevant clinical information was extracted from medical records. Multivariable logistic regression analyses were applied to identify correlates that were significantly associated with participation, high session attendance, high compliance with resistance and high compliance with endurance exercises. Results Participants were more likely to have higher education, be non-smokers, have lower psychological distress, higher outcome expectations, and perceive more exercise barriers than non-participants. In HI exercise, higher self-efficacy was significantly associated with high session attendance and high compliance with endurance exercises, and lower psychological distress was significantly associated with high compliance with resistance exercises. In LMI exercise, being a non-smoker was significantly associated with high compliance with resistance exercises and higher BMI was significantly associated with high compliance with resistance and endurance exercises. Furthermore, breast cancer survivors were less likely to report high compliance with resistance and endurance exercises in LMI exercise compared to survivors of other types of cancer. The discriminative ability of the multivariable models ranged from 0.62 to 0.75. Conclusion Several demographic, clinical and psychosocial factors were associated with participation in and adherence to exercise among cancer survivors. Psychosocial factors were more strongly associated with adherence in HI than LMI exercise. Trial registration This study was registered at the Netherlands Trial Register [NTR2153 ] on the 5th of January 2010.